Long-term challenges to Russian economic policy - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
Russia's economic growth slowed substantially over the past decade. To improve its long-term growth outlook, Russia must deal with structural problems. While the country has not lacked for ambitious development plans, the results of late have been rather thin. We discuss some of the key challenges facing the Russian economy and policy responses. Considering Russia's recent economic policy in light of the economic literature and potential reasons for its successes and failures, we suggest the focus of the country's current economic policy framework is too narrowly drawn to achieve a significant acceleration in long-term growth.
urn:nbn:fi:bof-202111302128
Keywords: 330; Russia; economic policy; development plans; economic growth